Die „schöpferische Indifferenz“ des „Nicht-Journalisten“: Karl Kraus’ jüdische Identitätsdiskurse im Licht und Schatten von Salomo Friedlaender, Dada und Gestalttherapie - Schütt, Günter (Acta Neophilologica, 2025)
This paper explores the relationship between Karl Kraus, Salomo Friedlaender, Dadaism, and Gestalt therapy in the context of anti-Semitic discourse and Jewish identity construction (1900–1933). Rather than the term “anti-journalist,” Friedlaender’s concept of “creative indifference” is proposed to describe Kraus’s subversive stance. The article examines Kraus’s connection to Friedlaender, stylistic parallels, and their relevance to Jewish self-positioning. Kraus’s attitude is interpreted as a universalist attempt to resist fixed identity by embracing creative detachment.